Juvenile waver as a mechanism of social stratification: a focus on human capital - Augustyn, Megan Bears (Criminology, 2017)
The historic transformations of the criminal justice system must be justified and interpreted through the effects on criminals (Maruna and Immarigeon, 2011). The push for harsher sentencing policies for juvenile offenders specifically through the use of juvenile waiver to criminal court is one such policy that is not well understood in terms of its effects on offenders, especially in terms of broader outcomes beyond recidivism. We use data from the Pathways to Desistance Study, which consists of a sample of adolescent offenders followed for 7 years postadjudication, to investigate the effect juvenile waiver has on human capital acquisition and yield among 557 adolescents from Maricopa County, Arizona. By using various matching specifications, our findings demonstrate that juveniles transferred to adult court experience no deleterious effects on human capital in terms of educational acquisition compared with similar youth retained in the juvenile system, yet they still earn considerably less income 7 years postadjudication. These results suggest that an important and unintended collateral consequence of juvenile waiver is an increase in social stratification potentially through labeling and labor market discrimination.